Analysis and synthesis of dual-band filters with controllable passbands - Sun, Xiaofeng (2015)
In this dissertation, recent contributions on dual-band filters are reviewed. For dual-bands, one important aspect of filter design is to have the center frequencies of desired bands being flexible. The other main aspect is to have the bandwidth of each desired band fully controllable. Until now, many methods have been developed to design dual-band filters. Some key methods utilized to implement filter design are summarized. Secondly, the synthesis of a novel dual-band bandpass filter with improved out-of-band performance is introduced. The proposed circuit is constructed by dual-band trisection stepped impedance resonators (SIRs) which can provide flexible center frequency and fully controllable bandwidth. Furthermore, we present a stepped-line inverter which can be used to realize a dual-band inverter. Thirdly, novel dual-order dual-prototype dual-band bandpass filters are proposed. Based on the dual-band resonator and dual-band inverter, these dual-band filters are specified not only to be different prototypes, but also in different orders. A dual-band filter with different prototypes and a dual-band filter with different orders are introduced first. Then a dual-order dual-prototype dual-band filter is proposed. Trisection stepped-impedance resonators are adopted as dual-band resonators. Stepped-impedance inverters are chosen as dual-band inverters. The trisection stepped-impedance resonator can also be used to replace the singleband resonators to control the harmonics of the first passband to avoid interfering with the second passband. Finally, some other multi-passband and ultra-wideband filters are discussed. The novel multi-passband filter is realized by using asymmetric radial stubs. Asymmetric radial stubs are formed from two single radial stubs in different dimensions. The transmission zeros of such asymmetric structure can be controlled by the respective radial stub. Using these symmetric radial stubs, the transmission zeros of the filter are realized. A novel ultra-wideband (UWB) filter is also realized by using coplanar-waveguide (CPW)-to-microstrip transition and stubs. This proposed filter is implemented by the CPW series stubs and microstrip shunt stubs. The transition includes a via that not only connects the series and shunt stubs, but also can improve the out-of-band rejection. All filters designed with the procedures developed in this dissertation are validated by several commercially available electromagnetic field-solver packages, along with measurements. To reduce the size, the structures of mentioned filters have been designed properly. The dimensions before and after tuning and optimization are provided. The excellent overall agreement between computational and experimental results verifies the advanced filter design procedures presented.